CUSTOMER COMPLAINT RESPONSE STRATEGY IN SERVICE FAILURE: STUDY OF ONLINE SHOPPER IN INDONESIA - Yeshika Alversia; Rizky Wijayanti (AFEBI Management and Business Review, 2019)
The shifting pattern of shopping habit into a digital nowadays perceived by the business players as the trigger of the growth in e-commerce and e-marketplace. Indonesia is currently one of the largest markets in Southeast Asia for online shopping. On the other hand, it is inevitable that there are still many obstacles and problems that defer the optimized growth of e-marketplace in Indonesia. There are customer concerns about issues that may arise when they do online shopping. Service failures that often arise eventually encourage customers to complain. Failure in service that lead to the emergence of various complaints from customers is an inevitable thing. Each company must prepare an optimal strategy to manage those complaints. The objective of this research is to find out whether there is a difference effect of service failure explanation in the form of excuse, justification, reference and apology on customer satisfaction and repurchase, in the high level of problem condition compared to the low level of problem condition, for the case of online shopper e-marketplace in Indonesia. Furthermore, this research is conducted with the purpose to build the best strategy of giving response using service failure explanation (i.e. excuse, justification, reference and apology). Researchers use a scenario-based experiment as the method and then all the data were analysed using T-test and ANOVA. Total 325 respondents of online shoppers in Indonesia were collected, and the results revealed that apology and justification are the best choices for responding customers’ complaints.